2018
DOI: 10.1002/adhm.201701469
|View full text |Cite
|
Sign up to set email alerts
|

Injectable, Tough Alginate Cryogels as Cancer Vaccines

Abstract: A covalently crosslinked methacrylated (MA)-alginate cryogel vaccine has been previously shown to generate a potent response against murine melanoma, but is not mechanically robust and requires a large 16G needle for delivery. Here, covalent and ionic crosslinking of cryogels are combined with the hypothesis that this will result in a tough MA-alginate cryogel with improved injectability. All tough cryogels can be injected through a smaller, 18G needle without sustaining any damage, while covalently crosslinke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 48 publications
2
90
1
Order By: Relevance
“…These pores can be adjusted to accommodate different types of cargo. For example, cryogels with larger pores are well-suited for antigens of a larger size, such as whole tumor cells, as they allow for immune cell infiltration while still efficiently encapsulating large cargo[184, 185]. Additionally, chemical modifications allow scaffold-based cancer vaccines to load almost all vaccine types, including nucleic acids, peptides, tumor lysates, and whole tumor cells[18, 186].…”
Section: Bridging Biomaterials and Cancer Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…These pores can be adjusted to accommodate different types of cargo. For example, cryogels with larger pores are well-suited for antigens of a larger size, such as whole tumor cells, as they allow for immune cell infiltration while still efficiently encapsulating large cargo[184, 185]. Additionally, chemical modifications allow scaffold-based cancer vaccines to load almost all vaccine types, including nucleic acids, peptides, tumor lysates, and whole tumor cells[18, 186].…”
Section: Bridging Biomaterials and Cancer Vaccinesmentioning
confidence: 99%
“…Results indicated that the cryogel cancer vaccine scaffold induced a higher survival rate in mice than the previously investigated PLGA cancer vaccine scaffold, when the same immunization schedule was applied[180]. However, the first generation cryogel was not mechanically robust enough to fit in a needle smaller than 16-gauge without damaging the cryogel[184]. Therefore, this cryogel required a more invasive 16 gauge needle, which created large wounds at the injection sites[184].…”
Section: Biomaterials Scaffolds For Localized Vaccine Deliverymentioning
confidence: 99%
“…These gels have large macroscale interconnected pores and improved mechanical properties compared to their mesoporous hydrogel counterparts 37 43 . These architectural features can allow easier nutrient inflow and waste removal, both of which are important in tissue engineering applications 42 , 44 . Furthermore, the highly dense polymer walls and large pores allow cryogels to undergo reversible compression (i.e., up to 90% of the initial volume) 37 , 42 , 44 , 45 .…”
Section: Introductionmentioning
confidence: 99%
“…These architectural features can allow easier nutrient inflow and waste removal, both of which are important in tissue engineering applications 42 , 44 . Furthermore, the highly dense polymer walls and large pores allow cryogels to undergo reversible compression (i.e., up to 90% of the initial volume) 37 , 42 , 44 , 45 . These cryogels have shape-memory properties and can undergo injection through hypodermic needles without any structural damage, allowing their minimally invasive delivery into the body 17 , 33 , 46 , 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the activated cells can migrate from scaffolds to secondary lymphoid organs and interact with other immune cells to provoke adaptive immune responses . Several 3D scaffolds such as alginate, polylactide‐ co ‐glycolide, mesoporous silica, and hydrogel have already been used to activate the immune system and inhibit tumor growth. Although these findings suggest that an implantable scaffold or an injectable hydrogel is a promising alternative for programing of host immune cells and for directing immune responses in vivo, long‐term activation of the immune system requires high loading and a slow and sustained release of the cargo from the carrier materials.…”
Section: Introductionmentioning
confidence: 99%